2007
DOI: 10.1002/cmdc.200700153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of System Structure–Function Relationships

Abstract: Preclinical pharmacology studies conducted with experimental medicines currently focus on assessments of drug effects attributed to a drug's putative mechanism of action. The high failure rate of medicines in clinical trials, however, underscores that the information gathered from these studies is insufficient for forecasting drug effect profiles actually observed in patients. Improving drug effect predictions and increasing success rates of new medicines in clinical trials are some of the key challenges curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…The integrative data representation and the predictive method discussed here fall within the scope of the emerging field of systems pharmacology (26). In recent years, systems pharmacologic approaches have been applied successfully to various problems, such as identifying new targets for existing drugs (23,24,(27)(28)(29)(30) or understanding ADEs (21,25,(31)(32)(33)(34)(35). Here, we extend our earlier work on developing network-based methods for predicting drug adverse events and drugdrug interactions.…”
Section: Discussionmentioning
confidence: 88%
“…The integrative data representation and the predictive method discussed here fall within the scope of the emerging field of systems pharmacology (26). In recent years, systems pharmacologic approaches have been applied successfully to various problems, such as identifying new targets for existing drugs (23,24,(27)(28)(29)(30) or understanding ADEs (21,25,(31)(32)(33)(34)(35). Here, we extend our earlier work on developing network-based methods for predicting drug adverse events and drugdrug interactions.…”
Section: Discussionmentioning
confidence: 88%
“…In the DRSN, the connections between drugs and subpathways revealed the drug dual effects on the human body. Some researchers have indicated that drugs binding to similar proteins tend to cause similar effects and these affected proteins may interact with each other to form a biological subpathway [21], [61][63]. Thus, if two drugs were connected to the same subpathways in our network, they were likely to cause the same therapeutic or side effects.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, Bork and colleagues, building from the knowledge from Fliri et al . that drugs with similar in vitro protein binding profiles trend towards displaying similar side effects, 74, 75 examined the side effects of 746 marketed drugs. 1018 drug-drug relations appeared, 261 of which exist from chemically dissimilar drugs in different therapeutic categories.…”
Section: Current Development In Molecular Network For Drug Discoverymentioning
confidence: 99%